THE EFFECT OF HIGH PERFORMANCE WORK SYSTEM ON EMPLOYEE SERVICE PERFORMANCE AND OCB WITH RESILIENCE AS A MODERATOR VARIABLE IN PT PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Salman Farisi; Yudi Siswadi; Jufrizen Jufrizen; Saidan Sany Lubis; Nurhayati Nurhayati (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
The purpose of this research is to determine the influence of the High Performance Work System on Employee Service Performance and OCB with Resilience as a Moderator Variable at Pt Perkebunan Nusantara Iii (Persero) Medan, both directly and indirectly. This research uses a quantitative approach and statistical analysis, namely partial least squares – structural equestion model (PLSSEM) which aims to carry out path analysis with latent variables. The research results show that the High Performance Work System (HPWS) has a significant and influential effect on Employee Service Performance at PT Perkebunan Nusantara III (Persero) Medan. High Performance Work System (HPWS) has a significant and influential effect on Organizational Citizenship Behavior (OCB) at PT Perkebunan Nusantara III (Persero) Medan. High Performance Work System (HPWS) has a significant and influential effect on Resilience at PT Perkebunan Nusantara III (Persero) Medan. Resilience has a significant influence on Employee Service Performance at PT Perkebunan Nusantara III (Persero) Medan. Resilience has a significant and influential effect on Organizational Citizenship Behavior (OCB) at PT Perkebunan Nusantara III (Persero) Medan.